Overcoming the Coordination Problem in New Marketplaces via Cryptographic Tokens - Bakos, Yannis; Halaburda, Hanna (Information Systems Research, 2022)
New platforms such as peer-to-peer marketplaces frequently face a “coordination problem” in attracting users, as potential users may be reluctant to join given the uncertainty of other users joining, and this could cause the new platform to fail. There are several mechanisms in the literature to help address this coordination problem, such as subsidies for early users and promises of refunds or buybacks if the platform fails; these mechanisms, however, are likely to favor incumbent and larger firms with established reputation and financial resources. Platform-specific tradable cryptographic tokens allow a platform such as a marketplace to trade future revenue for present revenue, which then can be used to address the coordination problem. If the new platform is capital-constrained, as is often the case for new entrants and unproven technology applications, then tokens can offer an attractive alternative. As this benefit results from the tradability of the tokens, regulators and policy makers should facilitate or at least not unduly constrain the issuance of tradable utility tokens by new platforms. There is no corresponding benefit from user anonymity, and thus no corresponding drawback from identity regulations to establish accountability.